Lucknow, then and now - Llewellyn-Jones, Rosie; Kapoor, Ravi.; National Centre for the Performing Arts (India) (Mumbai : Marg Publications on behalf of the National Centre for the Performing Arts, 2003)
Cultural history of Lucknow, India; contributed articles.
"Vol. 55, no. 1, September 2003"--T.p. verso; simultaneously issued in serial format as an issue of Mārg.
Includes bibliographical references (p. 146) and index.
Keywords: Lucknow (India) -- Civilization; Lucknow (India) -- Pictorial works